The impacts of oil price fluctuations on revealed comparative advantage of manufacturing commodities for ASEAN-5 economies - Azman Aziz, Mukhriz Izraf; Dahalan, Jauhari (2015)
This paper attempts to quantify the effects of oil price fluctuations on revealed symmetric comparative advantage (RSCA) for 95 manufacturing commodities of 5 ASEAN countries from 1991 to 2012.Using Zellner’s (1962) seemingly unrelated regression (SURE) model, oil price fluctuations negatively affect RSCA of more than 60% of the manufacturing commodities estimated. This is true especially for low-technology (LT1 & LT2) and medium-technology (MT3) commodities.The paper also found that endowment variables such as labour and capital stock significantly affects RSCA for more than 50% of the equations, giving support to Ricardian and Heckscher-Ohlin theorem of comparative advantage.